1999
DOI: 10.1007/s003930050170
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and radiological features of atlantoaxial joints in rheumatoid arthritis

Abstract: Atlantoaxial (AA) instability is frequent radiological finding in patients with rheumatoid arthritis (RA). Mostly no serious neurological disorders are expected in such patients. The purpose of the study was to assess the sagittal spinal canal diameter according to Steel's rule of third and its relationship to clinical symptoms. Radiological and clinical evaluation was performed in 65 in-patients with RA. Fifty four patients complained of neck pain, 39 had vertebrobasilar symptoms, and 25 mild neurological dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
2
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 16 publications
0
5
2
1
Order By: Relevance
“…Only one study of RA patients with CS disease showed correlation between clinical symptoms, neurological manifestations and radiological damage. 80 In the absence of clinical symptoms, if AAS or SAS or atlanto-axial impaction are present in the radiological assessment, then attention is required for surgical consultation. 15 , 81 …”
Section: Discussionmentioning
confidence: 99%
“…Only one study of RA patients with CS disease showed correlation between clinical symptoms, neurological manifestations and radiological damage. 80 In the absence of clinical symptoms, if AAS or SAS or atlanto-axial impaction are present in the radiological assessment, then attention is required for surgical consultation. 15 , 81 …”
Section: Discussionmentioning
confidence: 99%
“…Any patient with risk factors for development of ATS (rheumatoid arthritis, Down syndrome, congenital scoliosis, osteogenesisimperfecta, ankylosing spondylitis, neurofibromatosis) merits urgent radiographic and surgical evaluation [41].…”
Section: Miscellaneousmentioning
confidence: 99%
“…28 Areal bone mineral densities (measured in g/cm 2 ) were obtained along the occipital landmarks of interest (i.e., EOP, SNL, and INL) with a software scan setting for the forearm and subregional analyses of square regions of interest corresponding to 0.81 cm 2 . Values for regional volumetric bone mineral density (vBMD; measured in g/cm 3 ) were calculated by dividing the areal BMD of each region by the thickness of bone in that region as measured by calipers.…”
Section: Occipital Measurements and Bone Quality Analysismentioning
confidence: 99%